Degradable biomedical Zn-Cu-Mg alloy and treatment method thereof

By aging treatment of Zn-Cu-Mg alloys and controlling temperature and time, the problem of insufficient mechanical properties and biocompatibility in the medical field of zinc alloys is solved, and the mechanical properties and corrosion resistance of the alloys are improved.

CN119553111APending Publication Date: 2025-03-04SHIJIAZHUANG TIEDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411737771.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The application of existing zinc alloys in the medical field is limited by their poor mechanical properties, biocompatibility and degradation mechanisms, especially the poor plasticity, mechanical properties and corrosion resistance of materials after alloying and deformation processing.

Method used

By aging the Zn-Cu-Mg alloy, the treatment temperature (120℃~240℃) and time (1h~6h), the changes in the phase, mechanics, and corrosion resistance of the tissue are studied, and the optimal aging treatment process is determined.

Benefits of technology

It improves the mechanical properties and corrosion resistance of the alloy, uniformizes the structure, reduces the grain boundary segregation phenomenon, and achieves better biomedical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553111A_ABST
    Figure CN119553111A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of heat treatment of biomedical materials, in particular to a degradable biomedical Zn-Cu-Mg alloy and a treatment method thereof.The treatment method comprises the steps that zinc, copper and magnesium are sequentially subjected to vacuum induction melting and then cast, and an as-cast Zn-Cu-Mg alloy is obtained; and the as-cast Zn-Cu-Mg alloy is subjected to aging treatment, the Zn-Cu-Mg alloy subjected to aging treatment is obtained, the aging treatment temperature ranges from 120 DEG C to 240 DEG C, and the aging treatment time ranges from 1 h to 6 h. Aiming at the aging treatment problem of the degradable biomedical Zn-Cu-Mg alloy, the temperature and time of the aging treatment process are regulated and controlled, the change rule of the texture phase and the mechanical and corrosion resistance is researched, and then systematic research and analysis and comparison of data are carried out, so that the optimal aging treatment process is determined; and a new alternative material is provided for medical instruments such as heart stents and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment of biomedical materials, and in particular to a degradable biomedical Zn-Cu-Mg alloy and a treatment method thereof. Background Art

[0002] Biodegradable heart stents represent an innovative development in the field of cardiovascular interventional therapy, aiming to improve the treatment of patients with coronary artery disease. Degradable medical metal materials can gradually degrade and absorb after completing their functions in the body, thus reducing the need for secondary surgery for patients and alleviating unnecessary pain and financial pressure on patients. Therefore, the development of biomedical metal materials with biodegradable properties, including magnesium-based alloys, iron-based alloys, zinc-based alloys, etc., has become a research hotspot in the field of degradable metal materials.

[0003] Biodegradable metals, due to their unique biodegradability, bring scientific problems that are completely different from permanent implant materials, and also expand new application space. The most representative ones currently include magnesium-based, iron-based and zinc-based biodegradable metals. Zinc-based biodegradable medical metal materials have become a research hotspot in the biomedical field due to their excellent biocompatibility, suitable degradation rate and potential to promote bone growth. Although zinc-based biodegradable metals have obvious advantages in theory, current research is still insufficient, and modification and strengthening methods as well as degradation mechanisms need further study, which limits the development and utilization of zinc alloys in the medical field.

[0004] At present, the commonly used modification and strengthening treatment methods for zinc-based degradable metals include alloying, heat treatment, deformation treatment, surface treatment, etc. In 2007, Wang X et al. proposed that by adding suitable alloying elements, zinc alloy is expected to develop into a new type of biodegradable implant material. Studies have shown that the addition of magnesium can reduce the cytotoxicity of zinc alloys, but it also significantly reduces the plasticity of zinc alloys. Elements such as calcium and strontium are related to processes such as bone formation and calcification, and are not ideal choices for stent implantation. Although the addition of rare earth elements can also play a role in generating a second phase and strengthening grain boundaries, the intermetallic compounds formed by rare earths and zinc are not easy to degrade and absorb. Adding iron to zinc alloys can significantly improve the hardness and strength of the alloy and adjust the degradation rate of the alloy. Through rapid cooling and other means, the intermetallic compound FeZn formed by zinc and iron can be 13 Refinement is achieved, but the influence of Fe element on the polishability of zinc alloy cannot be ignored. 13The adverse effects on the polishing process of coronary stents may limit their application. Other non-essential or toxic elements, such as titanium and aluminum, although traditional zinc alloy components, may not be used in degradable coronary stent materials. The poor mechanical properties and biocompatibility of zinc restrict its clinical application. The poor mechanical properties of zinc can be improved by alloying, but its poor biocompatibility and adverse postoperative reactions are still the main problems that need to be solved.

[0005] Yuan et al. treated pure zinc with micro-arc oxidation surface modification, which can delay the corrosion of magnesium alloys, but accelerated the degradation of pure zinc, resulting in a further increase in the local concentration of zinc ions produced by degradation, resulting in higher cytotoxicity. Shearier et al. modified a layer of gelatin coating on the surface of pure zinc. The study found that cells can adhere and proliferate on the surface of pure zinc, but the adhesion situation is still somewhat different from that of the blank control group, indicating that the effect on improving the biocompatibility of zinc is limited. Traditional surface modification methods intensify the release of zinc ions, leading to higher cytotoxicity. After surface modification, the biocompatibility improvement effect of degradable medical zinc is insufficient.

[0006] At present, cast zinc alloys have obvious defects, such as uneven structure and stress concentration resulting in poor mechanical properties. The commonly used modification methods are alloying and deformation processing. The plasticity, mechanical properties and corrosion resistance of the materials after alloying and deformation processing are poor, which limits its application as a biomedical alloy. Summary of the invention

[0007] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a biodegradable biomedical Zn-Cu-Mg alloy and a treatment method thereof. The present invention regulates the temperature and time of the aging treatment process, studies the change law of the tissue phase, mechanics and corrosion resistance, and then conducts a systematic study. The data is analyzed and compared to determine the optimal aging treatment process, providing a new alternative material for medical devices such as heart stents.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0010] Zinc, copper and magnesium are sequentially subjected to vacuum induction melting and then cast to obtain a cast Zn-Cu-Mg alloy.

[0011] The cast Zn-Cu-Mg alloy is subjected to aging treatment to obtain the aged Zn-Cu-Mg alloy, wherein the aging treatment temperature is 120° C. to 240° C., and the aging treatment time is 1 h to 6 h.

[0012] The present invention aims at the problem that the existing alloying and deformation processing methods of cast zinc alloy have poor material plasticity, mechanical properties and corrosion resistance. The present invention performs aging treatment on biomedical Zn-Cu-Mg alloy. By adjusting the temperature and time of the aging treatment process, the variation law of the microstructure phase and mechanical and corrosion resistance is studied, so as to determine the best aging treatment process. The aging treatment temperature is 120℃~240℃, and the aging treatment time is 1h~6h. Cast Zn-Cu-Mg is composed of α-Zn (close-packed hexagonal structure), Mg2Zn 11 , MgZn2 three phases, the organization is mainly equiaxed α-Zn and α-Zn and Mg2Zn distributed along the crystal 11 After the aging process of the present invention, the eutectic structure is still mainly composed of α-Zn, Mg2Zn 11 The content of MgZn2 is reduced, while MgZn2 basically disappears, the degree of organizational homogenization is improved, and the grain boundary segregation phenomenon is significantly reduced, thereby improving the mechanical properties and corrosion resistance of the alloy.

[0013] In a preferred embodiment of the present invention, the aging treatment heating rate is 10° C. / min to 30° C. / min.

[0014] In a preferred embodiment of the present invention, the vacuum induction melting method is: first, 80wt.% to 90wt.% of zinc is melted at 450℃ to 600℃, and after the zinc is completely melted, copper and magnesium are added to melt at 800℃ to 850℃, and the temperature is kept for 5min to 15min, and finally 10wt.% to 20wt.% of the remaining zinc is added, and the temperature is lowered to 450min to 600℃, and the temperature is kept for 5min to 10min before casting.

[0015] In a preferred embodiment of the present invention, the purity of zinc is >99.99%, the purity of copper is >99.95, and the purity of magnesium is >99.99%.

[0016] In a preferred embodiment of the present invention, the composition of the cast Zn—Cu—Mg alloy includes Cu: 0.65 wt.% to 0.75 wt.%, Mg: 0.25 wt.% to 0.35 wt.%, and Zn: the balance.

[0017] In a preferred embodiment of the present invention, the as-cast Zn-Cu-Mg alloy phases include α-Zn, Mg2Zn 11 and MgZn2.

[0018] Another object of the present invention is to provide a degradable biomedical Zn-Cu-Mg alloy obtained by any of the above-mentioned treatment methods.

[0019] In a preferred embodiment of the present invention, the biodegradable Zn-Cu-Mg alloy is equiaxed, and the alloy phases include α-Zn and Mg2Zn 11 .

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. Aiming at the problem of poor material plasticity, mechanical properties and corrosion resistance in the existing alloying and deformation processing methods of cast zinc alloy, the present invention performs aging treatment on biomedical Zn-Cu-Mg alloy, and studies the variation law of microstructure, mechanical properties and corrosion resistance by regulating the temperature and time of the aging treatment process, so as to determine the best aging treatment process. The aging treatment temperature is 120℃~240℃, and the aging treatment time is 1h~6h. Cast Zn-Cu-Mg is composed of α-Zn (close-packed hexagonal structure), Mg2Zn 11 , MgZn2 three phases, the organization is mainly equiaxed α-Zn and α-Zn and Mg2Zn distributed along the crystal 11 After the aging process of the present invention, the eutectic structure is still mainly composed of α-Zn, Mg2Zn 11 The content of MgZn2 is reduced, while MgZn2 basically disappears, the degree of organizational homogenization is improved, and the grain boundary segregation phenomenon is significantly reduced, thereby improving the mechanical properties and corrosion resistance of the alloy.

[0022] 2. After the aging process of the present invention, the hardness of the Zn-Cu-Mg alloy increases first and then decreases with the increase of heating temperature and the extension of holding time. Under the dual effects of solid solution strengthening and fine grain strengthening, the hardness reaches a maximum of 87.75HV at 240°C for 2h. There is no order of magnitude difference in the electrochemical test data, and the corrosion tendency is relatively small. Due to the improvement of grain boundary segregation, the uniformity of the composition and precipitated phase in the grain is different, there is no obvious damage at the grain boundary, and there are obvious holes in the grain. The corrosion mechanism is galvanic corrosion due to the difference in potential difference between the second phase and the matrix, and the final corrosion form is mainly pitting. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 (a) XRD diagram and (b) metallographic structure diagram of the cast Zn-Cu-Mg alloy of the present invention.

[0024] Figure 2 The XRD patterns before and after different aging process treatments of the present invention are as follows; (a) 120°C to 320°C, 1h, (b) 240°C, 1h to 6h.

[0025] Figure 3 The metallographic structures of the present invention after aging treatment at different temperatures for 1 hour; (a) 120°C, (b) 240°C, (c) 320°C.

[0026] Figure 4 The metallographic structures of the present invention subjected to aging treatment at 240° C. for different holding times are shown; (a) 2h, (b) 4h, and (c) 5h.

[0027] Figure 5 This is the energy spectrum surface scanning analysis diagram of the cast state and after aging treatment at 240°C for 1h of the present invention.

[0028] Figure 6 The hardness variation curves of the alloy of the present invention under different conditions are as follows: (a) 120°C to 320°C, heating for 1 hour; (b) 240°C, heating for 1 hour to 6 hours.

[0029] Figure 7 Polarization curves of the present invention under different conditions: (a) 120°C to 320°C, heating for 1 h; (b) 240°C, heating for 1 h to 6 h.

[0030] Figure 8 Electrochemical corrosion morphology of the sample after treatment at 240℃×1h, (a) before removal of corrosion products; (b) after removal of corrosion products. DETAILED DESCRIPTION

[0031] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0033] Heat treatment is also a common method for modifying metal materials. Since the melting point of pure zinc is relatively low, at 419.5°C, the treatment temperature is relatively low, usually below 350°C. It can also be called aging treatment, that is, the material is kept at a certain temperature for a certain period of time and then cooled in a suitable cooling method to adjust the hardness, strength, corrosion resistance and other properties of the alloy material. At present, there are obvious defects in the cast Zn-Cu-Mg, such as uneven structure, stress concentration, etc., which cause poor mechanical properties. The commonly used modification methods are alloying and deformation processing, so further experiments are needed to explore the influence of heat treatment process on the structure and properties of zinc alloys. Therefore, the present invention attempts to use aging heat treatment to modify, uniform composition and structure, and study the changes in its structure and performance after treatment under different process conditions. The main research plans are as follows:

[0034] The cast substrate is made by vacuum induction melting. First, 80% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. At this time, the melting temperature is 800°C, and the mixture is kept warm for 10 minutes and stirred evenly. Finally, 20% of the remaining zinc is added, and the temperature is reduced to 600°C at the same time. After keeping warm for 5 to 10 minutes, the slag is removed and cast. The mold is preheated to 200°C before casting, and the alloy ingot is a round rod with a diameter of 50 mm.

[0035] According to the test requirements, a reasonable aging treatment process is formulated, and the temperature is raised and heated at a rate of 20°C / min based on the room temperature of 20°C, reaching the set temperature of 120°C to 320°C, and the corresponding insulation time is 1h to 6h, and finally cooled with the furnace. All aging treatments in the present invention are achieved using a box-type resistance furnace.

[0036] Subsequently, by analyzing the physical structure, hardness, electrochemical properties and corrosion morphology of the zinc alloy after aging treatment, the influence of aging treatment on its performance and corrosion and the corresponding mechanism were analyzed.

[0037] Example 1

[0038] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0039] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0040] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 240°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 2 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0041] Example 2

[0042] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0043] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0044] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 240°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 6 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0045] Example 3

[0046] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0047] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0048] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 240°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 4 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0049] Example 4

[0050] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0051] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0052] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 240°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 1 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0053] Example 5

[0054] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0055] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0056] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 120°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 1 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0057] Example 6

[0058] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0059] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0060] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 120°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 2 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0061] Example 7

[0062] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0063] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0064] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 120°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 4 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0065] Example 8

[0066] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0067] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0068] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 120°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 6 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0069] Comparative Example 1

[0070] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0071] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0072] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 360°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 1 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0073] Comparative Example 2

[0074] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0075] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0076] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 360°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 2 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0077] Comparative Example 3

[0078] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0079] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0080] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 360°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 4 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0081] Comparative Example 4

[0082] A method for treating a degradable biomedical Zn-Cu-Mg alloy comprises the following steps:

[0083] (1) The cast substrate is made by vacuum induction melting. First, 80wt.% of pure zinc with a purity of 99.99% is added to a graphite crucible at a melting temperature of 600°C. After the zinc is completely melted, copper with a purity of 99.95% and magnesium with a purity of 99.99% are added. The melting temperature is 800°C at this time. The mixture is kept warm for 10 minutes and stirred evenly. Finally, 20wt.% of residual zinc is added, and the temperature is lowered to 600°C at the same time. After keeping warm for 8 minutes, the slag is removed for casting. The mold is preheated to 200°C before casting. The alloy ingot is a round bar with a diameter of 50 mm.

[0084] (2) Aging treatment was performed in a box-type resistance furnace. The sample was first heated to 360°C at a heating rate of 20°C / min. After reaching the set temperature, it was kept warm for 6 h and finally cooled in the furnace to obtain the degradable biomedical Zn-Cu-Mg alloy after aging treatment.

[0085] Experimental Materials and Methods

[0086] The present invention selects cast Zn-Cu-Mg alloy as the research object, and the composition and content are shown in Table 1. The present invention adjusts the aging temperature in the aging process to 120°C to 320°C and the aging time to 1h to 6h, and uses X-ray diffraction, metallographic observation, scanning electron microscopy, electrochemistry and other means to analyze the influence of the aging treatment process on the material phase, organization and performance.

[0087] Table 1 Composition of cast Zn-Cu-Mg alloy (wt, %)

[0088] Zn Cu Mg margin 0.65~0.75 0.25~0.35

[0089] Figure 1 The XRD diagram and metallographic structure of the cast Zn-Cu-Mg alloy of the present invention are shown in FIG. Figure 1 (a) It can be seen that the alloy phase is composed of α-Zn, Mg2Zn 11 And a small amount of MgZn2. Figure 1 (b) The structure is relatively uniform, mainly equiaxed crystals and thin dendrites, with an average grain size of about 76 μm. In addition, the grains show different contrasts of light and dark. Under high magnification, it is found that the bright contrast area is the α-Zn solid solution structure, while the darker contrast area is the α-Zn and Mg2Zn solid solution structure. 11 Composed of lamellar eutectic structure.

[0090] Results Analysis

[0091] 1. Phase analysis

[0092] Figure 2 XRD patterns of Zn-Cu-Mg alloy after aging treatment, (a) 120℃~320℃, 1h, (b) 240℃, 1h~6h. It can be seen from the figure that after aging treatment, its phase is still mainly α-Zn, Mg2Zn 11 The MgZn2 content has decreased, while MgZn2 has basically disappeared, indicating that Zn x Mg y The phases are dissolved and the degree of component homogeneity is improved.

[0093] 2. Microstructure analysis

[0094] Figure 3 The metallographic structure of Zn-Cu-Mg alloy after aging treatment at different temperatures for 1h. As can be seen from the figure, with the increase of heating temperature, the microstructure morphology is basically the same, and it is still a relatively fine equiaxed crystal. According to the microstructure morphology, the contrast difference of the organization can be seen more intuitively, and the uniformity of the composition has changed significantly. Compared with the cast state, the difference in grain color contrast has decreased, and the composition has become more uniform. According to XRD phase analysis, the composition is more uniform at 120℃ and 240℃.

[0095] Figure 4 The metallographic structures of the aging treatment at 240℃ with different holding times are shown. It is found that with the extension of holding time, the microstructure is still fine equiaxed crystals and there is no obvious change. The structure is relatively stable and uniform, with little difference. The main difference is the change of contrast and grain size. The composition is relatively more uniform at 4h and 5h, but it may also be related to the location of the image. At 2h, the grains are obviously the smallest, with a grain size of about 57.32μm. After the holding time exceeds 2h, the grains tend to grow gradually.

[0096] In order to further analyze the effect of aging treatment on the element distribution of zinc alloy, energy spectrum analysis was performed on the alloy after casting and 240℃×1h aging treatment, such as Figure 5 As shown in the figure, Zn and Cu are evenly distributed in the matrix in the cast state, while Mg is enriched at the grain boundaries; after aging treatment, the Mg enriched at the grain boundaries dissolves back, making the three elements Zn, Cu, and Mg evenly distributed. This is consistent with the XRD results in the previous article, which shows that the Mg element dissolves back during the aging process, and the Mg-containing second phase (Zn x Mg y )reduce.

[0097] 3. Hardness analysis

[0098] Figure 6 The hardness change curves under different conditions are (a) 120℃~320℃, heating for 1h; (b) 240℃, heating for 1h~6h. It can be seen from the figure that the hardness after aging treatment is higher than that of the cast state. At the same time, with the increase of heating temperature and the extension of holding time, the hardness shows a change of first increasing and then decreasing. Under the same aging time, the hardness reaches the highest 84.67HV at 240℃. At this time, Zn x Mg y The phase is relatively small, but due to the element dissolution, the solid solution effect is enhanced, so the hardness reaches the highest. At 240℃, as the holding time increases, Zn x Mg y The phase content continued to decrease, and the solid solution strengthening was further enhanced. The grain size was the smallest when the temperature was kept warm for 2 hours. Under the combined effect of solid solution strengthening and grain refinement, the hardness reached the highest value of 87.75HV. As the time was further extended, the grains grew and the hardness showed a downward trend.

[0099] 4. Corrosion analysis

[0100] Polarization curves of samples in different states are as follows Figure 7 As shown in Figure 2, (a) 120℃~320℃, heating for 1h; (b) 240℃, heating for 1h~6h, with the increase of aging temperature and the extension of aging time, the corrosion potential E corr Basically unchanged, the corrosion current density I corr It increases first and then decreases, and the corrosion rate increases first and then decreases. Under the same aging time, the electrode current density at 240°C is larger, the corrosion rate is faster, and it is in an active dissolution state, indicating that the alloy undergoes electrode oxygen absorption reaction, and the anode polarization curve and cathode polarization curve are compared to the diffusion control area of ​​oxygen. Under the same aging temperature, the corrosion potential at 6h increases, the corrosion current density decreases, the corrosion rate slows down, and the corrosion resistance of the alloy improves.

[0101] According to the Tafel extrapolation method, the self-corrosion current Icorr , Self-corrosion potential E corr , cathode Tafel slope βc and other parameters. The results show that the self-corrosion potential E corr The difference is not big, and the rounded value is close to -1VSCE. The change trend is basically consistent with the OCP result. There is no order of magnitude difference overall. However, the corrosion rate at 240℃×6h is the smallest, which is 0.282mm / year. To a certain extent, it can be shown that its corrosion resistance is relatively excellent, which is in line with the degradation rate range of orthopedic internal fixation devices (0.2-0.5mm / year). Then, representative samples (240℃×1h) were selected for corrosion morphology observation, such as Figure 8 As shown in the figure, the surface corrosion was more serious before the corrosion products were removed, with obvious flocculent and spherical corrosion products; after the corrosion products were removed, it was found that the grain boundaries remained intact, and pits appeared inside the grains. This was because the second phase formed galvanic corrosion with the matrix, which accelerated the corrosion and formed pitting pits.

[0102] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0103] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for treating a degradable biomedical Zn-Cu-Mg alloy, characterized in that: The following steps are involved: Zinc, copper and magnesium are sequentially subjected to vacuum induction melting and then cast to obtain a cast Zn-Cu-Mg alloy; The cast Zn-Cu-Mg alloy is subjected to aging treatment to obtain the aged Zn-Cu-Mg alloy, wherein the aging treatment temperature is 120° C. to 240° C., and the aging treatment time is 1 h to 6 h.

2. The method for treating the degradable biomedical Zn-Cu-Mg alloy according to claim 1, characterized in that: The heating rate of the aging treatment is 10℃ / min~30℃ / min.

3. The method for treating the degradable biomedical Zn-Cu-Mg alloy according to claim 1, characterized in that: The vacuum induction melting method is: first melt 80wt.% to 90wt.% of zinc at 450℃ to 600℃, add copper and magnesium after the zinc is completely melted, melt at 800℃ to 850℃, keep warm for 5min to 15min, finally add 10wt.% to 20wt.% of residual zinc, cool to 450min to 600℃, keep warm for 5min to 10min, and then cast.

4. The method for treating the degradable biomedical Zn-Cu-Mg alloy according to claim 1, characterized in that: The purity of zinc is >99.99%, the purity of copper is >99.95%, and the purity of magnesium is >99.99%.

5. The method for treating the degradable biomedical Zn-Cu-Mg alloy according to claim 1, characterized in that: The composition of the cast Zn-Cu-Mg alloy includes Cu: 0.65wt.% to 0.75wt.%, Mg: 0.25wt.% to 0.35wt.%, and Zn: the balance, which is 100% in total.

6. The method for treating the degradable biomedical Zn-Cu-Mg alloy according to claim 1, characterized in that: The phases of cast Zn-Cu-Mg alloy include α-Zn, Mg2Zn 11 and MgZn2.

7. A degradable biomedical Zn-Cu-Mg alloy prepared by the preparation method according to any one of claims 1 to 6.

8. The degradable biomedical Zn-Cu-Mg alloy according to claim 7, characterized in that: The biodegradable Zn-Cu-Mg alloy is equiaxed crystal, and the alloy phases include α-Zn and Mg2Zn 11 .